Osnocy teorii adaptatsii i sportivnaya trenirovka - Pavlov, S. E. (Teorija i Praktika fiziceskoj Kul'tury, 1999)
The purpose of this paper was to consider the problem of the adaptation theory in the aspect of its influence on the technology of sports training. The author represents the retrospective analysis of the ideas, determining the content of the adaptation conceptions and criticizes F.S. Meyerson's concept of adaptation to physical loads in sports training. He considers that the contemporary system of sports training basing on this conception developed in L.P. Matveyev's and V.N. Platonov's articles is not effective and analyses the reasons of this situation.